Start-Up Subsidies and the Sources of Venture Capital - Hanna Hottenrott; Marius Berger (ZBW - Leibniz Information Centre for Economics, 2021)
Research suggests that public subsidies for newly founded firms have a positive effect on follow-on financing, in particular on Venture Capital (VC), through providing certification and early-stage liquidity. Building on the attention-based view, we argue that the various sources of VC value public start-up subsidies differently. This study is the first to differentiate between distinct types of investors who pursue different investment strategies. We show for a large sample of knowledge-intensive start-ups that there is indeed a correlation between subsidies and all sources of VC (Government VC, Independent VC, Corporate VC, and Business Angels). However, when accounting for firm characteristics that drive both selection into public subsidies as well as into VC financing through econometric matching techniques, subsidies are no longer linked to all types, but only to Government VC and Business Angel financing. We discuss possible explanations for this finding and implications for entrepreneurial finance.
Keywords: G24; L26; O25; O31; 330; Start-up Subsidies; Entrepreneurship Policy; Entrepreneurial Finance; VentureCapital; Business Angels